2013
DOI: 10.1063/1.4821240
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturating silicon with transition metals by ion implantation and pulsed laser melting

Abstract: We investigate the possibility of creating an intermediate band semiconductor by supersaturating Si with a range of transition metals (Au, Co, Cr, Cu, Fe, Pd, Pt, W, and Zn) using ion implantation followed by pulsed laser melting (PLM). Structural characterization shows evidence of either surface segregation or cellular breakdown in all transition metals investigated, preventing the formation of high supersaturations. However, concentration-depth profiling reveals that regions of Si supersaturated with Au and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 59 publications
(101 reference statements)
4
54
0
Order By: Relevance
“…It is the so-called growth interface breakdown or cellular breakdown due to the occurrence of constitutional supercooling in the melt [24][25][26][27] . At high enough impurity concentrations, a morphological instability occurs at the liquid-solid interface, resulting in the lateral segregation of Ti impurities and leading to a cellular solidification microstructure [24][25][26][27] . At low impurity concentration, the planar interface can still be kept but with surface segregation 19 .…”
Section: Resultsmentioning
confidence: 99%
“…It is the so-called growth interface breakdown or cellular breakdown due to the occurrence of constitutional supercooling in the melt [24][25][26][27] . At high enough impurity concentrations, a morphological instability occurs at the liquid-solid interface, resulting in the lateral segregation of Ti impurities and leading to a cellular solidification microstructure [24][25][26][27] . At low impurity concentration, the planar interface can still be kept but with surface segregation 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Diffusive velocities of transition metals are typically in the range of 10 2 -10 4 m/s, 13 and the equilibrium partition coefficient 16 for Ti in Si is 2 Â 10…”
Section: à3mentioning
confidence: 99%
“…[7][8][9] At high enough impurity concentrations, the liquid-solid interface can become morphologically unstable, leading to lateral segregation of the impurity and the formation of a cellular solidification microstructure. [10][11][12][13] This process, referred to as "cellular breakdown," results in copious excess impurity located in the "cell walls. "…”
Section: à3mentioning
confidence: 99%
“…During pulsed laser annealing the surface temperature exceeds the melting point, subsequently leading to liquid-phase epitaxial regrowth. The main problem of liquidphase epitaxy is the redistribution of impurities [18] and the cellular breakdown [19]. Alternatively, it has recently been demonstrated that millisecond range flash-lamp annealing (FLA) induces solid phase epitaxy which accounts for a complete recrystallization of the implanted layer at annealing temperatures below the melting point of substrate [20][21][22].…”
Section: Introductionmentioning
confidence: 99%